2022
DOI: 10.1155/2022/9124216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Pyroptosis-Related Prognosis Gene Signature and Immune Infiltration in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most heterogeneous malignancies worldwide with a dismal prognosis. Lack of efficient biomarkers, early detection, and prognosis is still a challenge for HCC. Pyroptosis is a new discovery inflammatory form of programmed cell death. There is growing evidence revealed that pyroptosis plays a role in physiological and pathological conditions of human cancers. However, the prognostic evaluation of these pyroptosis-related genes (PRGs) in HCC remains blank. Consensus clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Yu et al constructed a prognostic model with good predictive ability by extracting the pyroptotic genes in LIHC. The AUC areas for 1, 3, and 5 years were 0.748, 0.732, and 0.603, respectively [32]. In this study, the AUC of our prognostic model was 0.759, 0.658, and 0.654 at 1, 3, and 5 years, respectively.…”
Section: Mediators Of Inflammationsupporting
confidence: 52%
“…Yu et al constructed a prognostic model with good predictive ability by extracting the pyroptotic genes in LIHC. The AUC areas for 1, 3, and 5 years were 0.748, 0.732, and 0.603, respectively [32]. In this study, the AUC of our prognostic model was 0.759, 0.658, and 0.654 at 1, 3, and 5 years, respectively.…”
Section: Mediators Of Inflammationsupporting
confidence: 52%
“…Based on previous publications, 5 prognostic risk models were selected, including 8-gene [18], 8-gene [19], 10-gene [20], 2-gene [21], and 5-gene signatures [22], and compared these signatures with our model. Te rms package in R was employed to calculate the concordance index (C-index) of the various signatures and to compare the prediction performance of these models in HCC samples.…”
Section: Comparison Of Diferent Signaturesmentioning
confidence: 99%
“…As expected, the OS of samples with a high and low risk score and ROC and KM analysis findings (Supplementary Figure S10) were consistent with TCGA database analysis results (Figure 7). In addition, we conducted a multivariate Cox analysis to compare the prognostic model with four published models ( [15][16][17][18]) using the C-index. The prognostic model in our study achieved a higher C-index than the other four published models (Supplementary Figure S11).…”
Section: Construction Of Prognostic Model and Validationmentioning
confidence: 99%
“…Finally, the correlation between the prognostic model and clinicopathological features was analyzed. 16,880 specific cells, screened from the single-cell expression profile matrix, were divided into 20 sub-clusters. Cell typing revealed that 97% of these cells corresponded to HCC cell lines, demonstrating the high specificity of cells derived from single-cell sequencing.…”
mentioning
confidence: 99%